Porta-enxertos para a lima-ácida-'Tahiti' na região de Bebedouro, SP - Figueiredo, José Orlando De; Stuchi, Eduardo Sanches; Donadio, Luiz Carlos [UNESP]; Teófilo Sobrinho, Joaquim; Laranjeira, Francisco Ferraz; Pio, Rose Mary; Sempionato, Otávio Ricardo (Sociedade Brasileira de Fruticultura, 2002)
In 1988 an experiment was established in Bebedouro, SP (Brazil), in order to evaluate eleven rootstocks for 'Tahiti' lime (Citrus latifolia Tanaka). Scion variety was the IAC 5 cultivar, from IAC germplasm bank at Cordeirópolis, SP; all rootstocks were also obtained at that institution. A randomized blocks design was used as statistical model, with eleven blocks and one plant per treatment. The eleven treatments were: 'Sunki' (Citrus sunki Hort. ex Tanaka), 'Cleópatra'(Citrus reshni Hort. ex Tan.), 'Batangas' and 'Oneco' (Citrus reticulata Blanco) mandarins; EEL trifoliate (Poncirus trifoliata Raf.); Rangpur lime (Citrus limonia Osbeck); 'Catania 2 Volkamer' lemon (Citrus volkameriana Tan. & Pasq.); 'Orlando' tangelo (C. reticulata Blanco x C. paradisi Macf.); 'Swingle' citrumelo (P. trifoliata Raf. X Citrus paradisi Macf.); 'Morton' citrange (P. trifoliata Raf. X C. sinensis (L.) Osbeck) and 'Caipira DAC' sweet orange (C. sinensis (L.) Osbeck). Yield was evaluated annually from 1991 to 1998; drought resistance was evaluated in 1991, 1994 and 1995; fruit features were assessed in 1997 and canopy height and diameter were measured in 2000. Highest mean yields were associated to 'Orlando' tangelo, 'Morton' citrange and 'Swingle' citrumelo rootstocks. The lowest yields were related to mandarins and 'Caipira DAC' sweet orange. Plants with 'Rangpur' lime as rootstock bore intermediate yields and their productive life was short.

Foi instalado um experimento de seleção de porta-enxertos para a lima-ácida-'Tahiti' (Citrus latifolia Tanaka), em dezembro de 1988, na Estação Experimental de Citricultura de Bebedouro-SP, com o objetivo de conhecer seu comportamento e oferecer novas opções de plantio para as condições ecológicas semelhantes às daquela região. A variedade copa, originária do BAG-Citros do IAC, localizado no Centro de Citricultura Sylvio Moreira, Cordeirópolis-SP, é um clone nucelar de 'Tahiti', denominado IAC-5. Os porta-enxertos, que tiveram a mesma origem, foram: tangerinas-'Sunki' (Citrus sunki Hort. ex Tanaka); 'Cleópatra'(Citrus reshni Hort. ex Tan.); 'Batangas' e 'Oneco' (Citrus reticulata Blanco); trifoliata-EEL (Poncirus trifoliata Raf.); limão-'Cravo' (Citrus limonia Osbeck); limão-'Volkameriano Catania 2' (Citrus volkameriana Tan. & Pasq.); tangelo-'Orlando' (C. reticulata Blanco x Citrus paradisi Macf.); citrumelo-'Swingle' (P. trifoliata Raf. X C.paradisi Macf.); citrange-'Morton' (P. trifoliata Raf. X C. sinensis (L.) Osbeck) e laranja-'Caipira DAC' (C. sinensis (L.) Osbeck). Com relação à produção, avaliada no período de 1991 a 1998, os porta-enxertos de melhor comportamento foram o tangelo-'Orlando', citrange-'Morton' e citrumelo-'Swingle'. As mais baixas produções ocorreram nos porta-enxertos de tangerina e de laranja-'Caipira DAC'. O limão-'Cravo' apresentou produção intermediária e proporcionou curta vida útil às plantas.
Rootstocks for 'Tahiti' acid lime in Bebedouro region, SP, Brazil
Keywords: selection; Citrus latifolia; yield; citrus; seleção; Citrus latifolia; produção; citros